Strengthening social innovation in higher education institutes - an organizational change process involving staff and students - Prantl, Judith; Freund, Susanne; Kals, Elisabeth (Social Enterprise Journal, 2021)
Purpose In recent decades, higher education institutes (HEIs) have come under pressure to cooperate with society as a whole. This shift towards an increased focus on third mission and social innovation activities implies a substantial organizational change process for many HEIs, as they need to initiate both structural and cultural changes. This paper provides guidance for such change processes by examining the views and attitudes of academic and administrative staff, as well as students within the HEIs over a period in which the HEIs increase their focus on social innovation. Design/methodology/approach The study uses a longitudinal quantitative approach consisting of a survey of administrative and academic staff, as well as students at two German HEIs. The authors studied members' attitudes towards third mission and social innovation activities (N = 3470). Findings Results suggest that the university members' attitudes towards third mission and social innovation are positive but change to some extent over time. Different aspects shape the attitudes within the three groups (administrative staff, academic staff and students). Furthermore, attitudes vary among academic employees who are involved in the process and those who are not. Practical implications The findings provide useful information for university managers and anyone aiming to promote social innovation at HEIs. Originality/value The study examines how attitudes of university members change whenever social innovation takes place at HEIs. This study includes data on the participation and empowerment of all HEI members in view of the important role that HEIs can play as supporters of social innovation.
Keywords: Innovation sociale; Rôle des universités; Université

Strengthening social innovation in higher education institutes - an organizational change process involving staff and students - Prantl, Judith; Freund, Susanne; Kals, Elisabeth (Social Enterprise Journal, 2021)
Purpose In recent decades, higher education institutes (HEIs) have come under pressure to cooperate with society as a whole. This shift towards an increased focus on third mission and social innovation activities implies a substantial organizational change process for many HEIs, as they need to initiate both structural and cultural changes. This paper provides guidance for such change processes by examining the views and attitudes of academic and administrative staff, as well as students within the HEIs over a period in which the HEIs increase their focus on social innovation. Design/methodology/approach The study uses a longitudinal quantitative approach consisting of a survey of administrative and academic staff, as well as students at two German HEIs. The authors studied members' attitudes towards third mission and social innovation activities (N = 3470). Findings Results suggest that the university members' attitudes towards third mission and social innovation are positive but change to some extent over time. Different aspects shape the attitudes within the three groups (administrative staff, academic staff and students). Furthermore, attitudes vary among academic employees who are involved in the process and those who are not. Practical implications The findings provide useful information for university managers and anyone aiming to promote social innovation at HEIs. Originality/value The study examines how attitudes of university members change whenever social innovation takes place at HEIs. This study includes data on the participation and empowerment of all HEI members in view of the important role that HEIs can play as supporters of social innovation.
Keywords: Innovation sociale; Rôle des universités; Université